Evolution PDEs with nonstandard growth conditions : existence, uniqueness, localization, blow-up /: existence, uniqueness, localization, blow-up. (2015) - Antont︠s︡ev, S. N (Stanislav Nikolaevich); Shmarev, S. I
No abstract available